PEMANFAATAN TEKNOLOGI INFORMASI SEBAGAI SUMBER BELAJAR GUNA MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN AKIDAH AKHLAK DI MA MATHLA’UL ANWAR KECAMATAN KEDONDONG KABUPATE PESAWARAN - SOLIHUN; AGUS SUJARWO; MUJIYATUN (UNISAN JURNAL, 2022)
This study discusses the use of information technology as a learning resource in order to improve student learning outcomes in Akidah Akhlak Subjects at MA Mathla'ul Anwar, Kedondong District, Pesawaran Regency. The focus of this research is on matters relating to how to use information technology as a learning resource in order to improve student learning outcomes in the subjects of Akidah Akhlak Subjects at MA Mathla'ul Anwar, Kedondong District, Pesawaran Regency. The data collection techniques used were interviews, observations, and documentation. Against the MA Mathla'ul Anwar agency, Kedondong District, Pesawaran Regency in the use of information technology as a learning resource in order to improve student learning outcomes in Akhlak Akidah Subjects at MA Mathla'ul Anwar, Kedondong District. Pesawaran Regency.The data were obtained by means of observation, direct interviews, and documenting, Islamic religious subject teachers and students, teachers have used information technology as a learning resource, namely learning by using information technology that is available at school as a learning tool, such as laptops, internet, LCDs. and projector. The results showed that. First, the use of information technology in Islamic religious subjects, teachers use learning by using existing technological equipment such as laptops, LCDs, power points, and the internet. Through this information technology, students easily accept the material presented by the teacher and students' learning activities in the classroom are more active, the classroom atmosphere is conducive so that learning will be more effective and efficient and does not look monotonous. Both teachers can take advantage of information technology because they want to grow their students' enjoyment of Islamic religious subjects. It is proven that students who receive material by seeing and hearing will always remember it, understand and know.